The Experiences of Selected Teachers in Dasmarinas City During the Initial Implementation of Online Distance Learning (ODL) in the Philippines - Barrera, Lannie; Gomez, Abigail C.; Padernos, Jessy Lou F.; Jr., Primo P. Villanueva; Espinosa, Mark Jayson G. (Future Science / FSH-PH Publications, 2022)
The challenges brought about by the COVID- 19 pandemic was not only on the health, economic, and medical sector. It also brought about drastic changes to the education sector. With the